Characterisation of biocondensate microfluidic flow using array-detector FCS - Dilissen, Stijn; Silva, Pedro L.; Smolentseva, Anastasia; Kache, Tom; Thoelen, Ronald; Hendrix, Jelle (Biochimica et biophysica acta. General subjects, 2024)
Biomolecular condensation via liquid-liquid phase separation (LLPS) is crucial for orchestrating cellular activities temporospatially. Although the rheological heterogeneity of biocondensates and the structural dynamics of their constituents carry critical functional information, methods to quantitatively study biocondensates are lacking. Single-molecule fluorescence research can offer insights into biocondensation mechanisms. Unfortunately, as dense condensates tend to sink inside their dilute aqueous surroundings, studying their properties via methods relying on Brownian diffusion may fail. We take a first step towards single-molecule research on condensates of Tau protein under flow in a microfluidic channel of an in-house developed microfluidic chip. Fluorescence correlation spectroscopy (FCS), a well-known technique to collect molecular characteristics within a sample, was employed with a newly commercialised technology, where FCS is performed on an array detector (AD-FCS), providing detailed diffusion and flow information. The AD-FCS technology allowed characterising our microfluidic chip, revealing 3D flow profiles. Subsequently, AD-FCS allowed mapping the flow of Tau condensates while measuring their burst durations through the stationary laser. Lastly, AD-FCS allowed obtaining flow velocity and burst duration data, the latter of which was used to estimate the condensate size distribution within LLPS samples. Studying biocondensates under flow through AD-FCS is promising for single-molecule experiments. In addition, AD-FCS shows its ability to estimate the size distribution in condensate samples in a convenient manner, prompting a new way of investigating biocondensate phase diagrams. We show that AD-FCS is a valuable tool for advancing research on understanding and characterising LLPS properties of biocondensates. [Display omitted] •Array detector FCS can be used to characterize the flow in microfluidic channels.•Flowing Tau condensates show promising burst durations for single-molecule research.•Microfluidic array detector FCS can be used to analyse condensate size distributions.